2017
DOI: 10.1111/apa.14123
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study showed that the quality of life of Finnish adolescents with cerebral palsy continued to be relatively good

Abstract: We showed that QoL was relatively good in childhood and adolescence. The Finnish version of the CP QOL-Teen questionnaire was an appropriate clinical tool for assessing QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Böling et al. report the findings of their study on the quality of life of Finnish adolescents with CP, which indicated that it continued to be relatively good.
…”
Section: Changing Pattern Of Cerebral Palsy In Swedenmentioning
confidence: 99%
“…Böling et al. report the findings of their study on the quality of life of Finnish adolescents with CP, which indicated that it continued to be relatively good.
…”
Section: Changing Pattern Of Cerebral Palsy In Swedenmentioning
confidence: 99%
“…In terms of the stability of quality of life assessment in longitudinal samples, both Rapp et al [ 27 ] in the international SPARCLE cohort, as well as Böling et al [ 28 ] using a Finnish sample, provided evidence using longitudinal studies that QoL in young participants with CP displays stability from childhood to adolescence, despite a parallel decrease in adolescents with CP and from the general population in several domains. Also, in their comparative cross-sectional study of CP and healthy controls grouped into children, adolescents and emerging adults (age range: 6–30 years), Riquelme et al [ 29 ] showed that age-group had no significant influence on QoL for individuals with CP.…”
Section: Introductionmentioning
confidence: 99%
“…For example, “access to services” plays a different role throughout the world. 13 14 18 19 20 23 24 31 In our cohort, this resulted in a high number of missing values. Furthermore, the question “how happy are you?” in the domain “family health” may not aim in the same direction as other questions in the domain, which had a negative effect on Cronbach's α and, therefore, on internal consistency.…”
Section: Discussionmentioning
confidence: 96%
“…For example, "access to services" plays a different role throughout the world. 13,14,[18][19][20]23,24,31 In our cohort, this resulted in a high number of missing values. Furthermore, the question "how happy are you?"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation